Genetic testing women with newly diagnosed breast cancer: What criteria are the most predictive of a positive test?. (21st December 2022) - Metcalfe, Kelly A.; Narod, Steven A.; Eisen, Andrea; Poll, Aletta; Zamani, Neda; McCready, David; Cil, Tulin D.; Wright, Frances C.; Lerner‐Ellis, Jordan; McCuaig, Jeanna; Graham, Tracy; Sun, Ping; et al.
Abstract: Background: Knowledge of pathogenic variants in cancer‐predisposing genes is important when making breast cancer treatment decisions, but genetic testing is not universal and criteria must be met to qualify for genetic testing. The objective of this study was to evaluate the pathogenic variant yield for nine cancer predisposition genes by testing criteria, singly and in combination. Methods: Women diagnosed with breast cancer between June 2013 and May 2018 were recruited from four centers in Toronto, Canada. Participants completed a demographics and family history questionnaire and clinical characteristics were collected from medical charts. Genetic testing was done for BRCA1, BRCA2, PALB2, ATM, CHEK2, BRIP1, RAD51D, RECQL, and TP53 . Pathogenic variant frequencies were calculated according to five criteria (age ≤ 50, triple‐negative breast cancer, family history, bilateral breast cancer, or Jewish ethnicity). Results: Of the 1006 women studied, 100 women (9.9%) were found to have a pathogenic variant in one of the nine genes tested. The highest prevalence of pathogenic variants was found in women with triple‐negative breast cancer (23%). Of the 100 pathogenic variants detected, 78 were detected in women diagnosed at age 50 or less. A total of 96% of the mutations were identified with three criteria (age of diagnosis, family history, and triple‐negative status). Conclusions: Genetic testing criteria for women with breast cancer should include women with triple‐negative breast cancer, regardless of age. All women aged 50 years or below at time of breast cancer diagnosis should be offered genetic testing. Abstract : All genetic testing criteria evaluated resulted in at least a 10% pathogenic variant positive rate, with the highest being in women with triple negative breast cancer (23.2%). For women who only met one of the identified criteria, positivity rates ranged between 2.0% (Jewish ethnicity) to 14.3% (synchronous bilateral breast cancer).